STRATEGI KEBIJAKAN GENDER ANALYSIS PATHWAY (GAP) UNTUK MENYELESAIKAN MASALAH SOSIAL BUNUH DIRI DI KABUPATEN GUNUNGKIDUL - Intan Nisaaul Chusna; Alinda Mega Karismalia; Megawati Sukarno Putri; Eka Zuni Lusi Astuti (Jurnal PPI Dunia, 2022)
Gunungkidul Regency is an area a high number of suicides. The majority of perpetrators of suicide are elderly and male, so it is inversely proportional to several social studies that WHO have been carried out that the perpetrators of suicide are dominated by women and under 70 years of age for the Southeast Asia region. Responding to these phenomena is considered important for a government preventive policy in Gunungkidul through a gender mainstreaming policy approach. The gender policy formulation method chosen is the Gender Analysis Pathway (GAP). The purpose of this study was to describe the causes of the majority of elderly and mal individuals to commit suicide and the GAP policy strategy for preventive efforts in problem of suicide. The writing method used is a literature study with online secondary data. The result is that physical, psychological, and environmental faktor s encourage the elderly to suicide, the masculine culture that is still strong in Gunungkidul encourages men to suicide and GAP can be used as a method in formulating policies for dealing with suicide cases by related institution.